PENINGKATAN LITERASI KEUANGAN PADA TOKO BATIK RIFKI HADI MELALUI PENDAMPINGAN PEMBUKUAN SEDERHANA - Lulu Nailufaroh; Neneng Sri Suprihatin; Dian Maulita (LP3M STKIP MUHAMMADIYAH MUARA BUNGO, 2022)
This community service aims to provide socialization about simple bookkeeping for Toko Batik Rifki Hadi. Also The purpose of this PKM is to assist in the preparation of MSME financial report bookkeeping with simple techniques. So that measurable income, expenses and profits are obtained and know the development of their business. The method of implementing community service in Toko Batik Rifki Hadi is divided into three stages, namely the initial stage of training, the second stage is the implementation of training and mentoring, and the final monitoring. The results obtained from this activity are able to increase knowledge and skills in running a business through simple bookkeeping/records that are easily applied